Fundamental studies of large area and high aspect ratio UV embossing - Zhou, Wenxiu (2008)
Large area molding of long and deep microchannels and microgrids array separated by high aspect ratio microwalls are important for high sensitivity and high throughput microfluidic and micro-optical devices. Ultraviolet (UV) embossing has been shown to be a feasible, economical and efficient method for replication of such microstructures. Specially formulations were successfully used for high aspect ratio (7-9) UV embossings over a 100mm-diameter area and very high aspect ratio (>10) UV embossing. Some challenges arose but the optimization of the processing resolved the difficulties. To understand the effect of resin properties on stress build-up and network evolution, formulations varies molecular weight were studied from conversion, polymerization rate, shrinkage, modulus and stress development and their inter-relation. To improve replication fidelity and achieve easy demolding, the effect of release additive on the cured resin surface was investigated. The selective segregation was beneficial to demolding since only small amount of release additive added can result in large decrease of the mold-resin interfacial energy difference leading to easy demolding and high replication fidelity.